Evaluation Capacity Building and Improvement of Monitoring and Evaluation practice among Non- Governmental Organizations in Central Eastern Counties of Kenya - Kithinji Cavens (European Scientific Journal, ESJ, 2019)
Monitoring and evaluation (M&E) in projects management is an expensive but critical process that needs careful implementation because of its role in providing information necessary for decision making, planning, and policy formulation. This importance has occasioned the need to look into the quality of M&E process and a lot of effort has been put into building capacity of M&E stakeholders in projects and programs. The goal of this study was to establish evaluation capacity building (ECB) efforts and the influence of the same on general M&E practice among non-governmental organization in central eastern counties of Kenya. The study was guided by pragmatism paradigm to conduct a descriptive survey. Stratified random sampling was used to obtain the sample studied. A structured questionnaire with Likert-type questions, anchored on a five-point scale was used to collect primary data which was triangulated using data from interviews. The findings were that organisations in the region are doing a number of unstructured activities to build evaluation capacity which are done in varying degrees, these activities had influence on M&E practice. The study recommends organizations to invest in ECB activities especially those that build capacity in M&E professional development and building M&E support structures because these were perceived to contribute more to improved M&E practice. However they need to be systematized and balanced in addressing the M&E capacity need. Organizations needs to put more resources into. There is also a need to establish and test an ECB model that would be used in a simple in the region.